Communication and Resolving Conflicting Situations: Indispensable in Forming Cordial and Amiable Terms and Relationships with others (Indian Journal of Social Science and Literature (IJSSL), 2024)
Throughout the lives of the individuals, irrespective of communities, occupations, categories and socio-economic backgrounds are required to be well-versed in terms of communication skills. These are the skills that are facilitating in not only augmenting knowledge in terms of various factors, but also individuals are able to form cordial and amiable terms and relationships with others. It is apparently understood that in some cases, there are occurrences of conflicting situations and disagreements among Individuals. These are regarded as the major barriers within the course of development of mutual understanding, hence, it is vital for individuals to be well-versed in terms of peaceful conflict resolution methods. These are facilitating in creating a pleasant and peaceful environment. One of the important aspects that needs to be taken into account is, the individuals need to form positive viewpoints in terms of various factors. Furthermore, they are required to be treated with respect and courtesy. In this manner, communication skills will be honed and peaceful conflicting resolution methods will be put into operation in an efficient manner. In this manner, individuals will render an important contribution in bringing about improvements in their overall personality traits and living conditions. Therefore, it is well-understood, communication and resolving conflicting situations is indispensable in forming cordial and amiable terms and relationships with others. The main concepts that are taken into account in this research paper are, understanding the meaning and significance communication and resolving conflicting situations, measures to be implemented in honing communication skills and understanding peaceful conflict resolution methods.